ANALYSIS OF CONSUMER AWARENESS OF ENVIRONMENTALLY FRIENDLY PRODUCTS IN MANADO - Pangkong, Blessy Monica; Pangemanan, Sifrid S.; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Consumer awareness is the source that supports people to make a decision and make the right choice. That is why consumer awareness is an important thing to supports the learning of consumer behavior. This study expects to give useful information regarding consumer awareness toward green products so that, the green marketer can increase or even innovate their strategies in green marketing. To achieve these objectives the researcher got information from 15 informants using qualitative study which is an in-depth interview. Meanwhile, in-depth interview is used to collect the data among the respondents which are Manado citizens as environmentally friendly productsâ€™ consumers. The results showed consumers in Manado are still lacking of environmentally friendly products awareness. Proven by their behavior which shows the infrequently usage of environmentally friendly products. This study suggested that better-educated consumers should understand environmental issues and giving more effort to concern about the environment. As well as involved and motivated to participate in environmentally responsible behaviors, especially in using and aware of environmentally friendly products.Â Keywords: environmentally friendly product, consumer awareness, green marketing